Pendidikan Mindset Menabung Yang Benar Bagi Santri Di Pesantren Tahfidz Al-Qur’an Izzuddin - Yuliani, Yuliani; Malinda, Shelfi; Efriani, Betharia; Mora Siagian , Belinda; Hermanto, Hermanto (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program aims to improve financial literacy and develop a proper saving mindset among students (santri) of Tahfidz Al-Qur’an Izzuddin Islamic Boarding School in Palembang. The low awareness of saving behavior among adolescents, including santri, is often caused by the lack of education on personal financial management. The program adopted a participatory-educational approach through several stages: socialization, training, mentoring, and evaluation. A total of 19 students from grades VII–IX actively participated in this activity. The materials covered the fundamentals of saving, factors that hinder saving habits, effective saving techniques, and an introduction to various saving and investment instruments. The results indicated a significant improvement in participants’ understanding of the importance of saving, personal financial management, and their ability to formulate short- and long-term financial goals. Evaluation results showed that 90% of participants understood effective saving techniques, and 100% were able to identify their personal financial goals. This program successfully fostered early financial awareness and served as an initial step toward building the students’ economic independence through planned and sustainable saving habits.